IMPORTANCE OF USING FRACTAL GRAPHICS SOFTWARE IN THE EDUCATIONAL PROCESS - Ergashev, M (Журнал математики и информатики, 2024)
This paper explores the significance of fractal graphics software in education, highlighting its applications in mathematics, computer programming, art, and the natural sciences. The use of fractal graphics software allows students to visually and interactively engage with mathematical concepts, fostering a deeper understanding of geometry, algebra, and calculus. Additionally, it serves as a valuable tool for developing programming skills by enabling students to manipulate algorithms and even write custom code. Beyond mathematics, the incorporation of fractal graphics into the curriculum enhances artistic creativity, inspiring students to explore the intersection of math and art. The paper also underscores the relevance of fractals in various scientific fields, such as astrophysics and biology, where fractal geometry proves instrumental in modeling complex natural phenomena. Furthermore, the application of fractals in computer graphics, image compression, and special effects in the entertainment industry is discussed. In conclusion, the paper emphasizes the multifaceted educational benefits of fractal graphics software, promoting a holistic and interactive learning experience across diverse disciplines.